Genetic diversity of Venturia carpophila populations from different hosts and geographic regions in China - Zhou, Yang; Chaisiri, Chingchai; Luo, Mei; Fan, Fei; Wang, Yu-Fu; Yin, Liang-Fen; Yin, Wei-Xiao; Luo, Chao-Xi (Frontiers in Microbiology, 2022)
Venturia carpophila, the causal agent of scab disease of peach, mume and apricot, is widely distributed around the world. Scab of stone fruits is an important disease in China. However, little is known about the population biology and genetic diversity of the V. carpophila. To better understand the genetic diversity and population structure of V. carpophila, 186 single-spore isolates from different hosts and geographic regions were obtained and analyzed by using 31 simple sequence repeat (SSR) markers. This included 156 isolates from peach spanning 14 provinces, 15 isolates from mume and 15 isolates from apricot in Huazhong Agricultural University (HZAU). Diversity analysis with SSR markers showed a low incidence of polymorphisms within mume isolates (32.59% of markers), but higher incidence of polymorphisms within peach isolates (42.96%) and apricot isolates (57.04%). Within peach isolates, Nei’s average gene diversity ranged from 0.07 for Hebei population to 0.18 for Hubei population. AMOVA analysis revealed that 13% of the observed genetic diversity was partitioned among the geographic populations, while 40% of the observed genetic diversity was partitioned among the host populations. Other analyses (PCoA, STRUCTURE, DAPC, MSN, and UPGMA) all indicated that the Chinese V. carpophila populations could be clustered into three distinct genetic groups, which were corresponded to the host boundaries of peach, mume and apricot. The genetic identity of V. carpophila isolates throughout the range is dependent on hosts, but not geographic regions.